2019
DOI: 10.1016/j.bpj.2019.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Entropy as a Proposed Gating Mechanism for Magnetogenetic Ion Channels

Abstract: Magnetically sensitive ion channels would allow researchers to better study how specific brain cells affect behavior in freely moving animals; however, recent reports of ''magnetogenetic'' ion channels based on biogenic ferritin nanoparticles have been questioned because known biophysical mechanisms cannot explain experimental observations. Here, we reproduce a weak magnetically mediated calcium response in HEK cells expressing a previously published TRPV4-ferritin fusion protein. We find that this magnetic se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 79 publications
0
52
0
Order By: Relevance
“…While several groups have reproduced the key observation that a sufficiently strong magnetic field can gate TRPV1 [15][16][17] and TRPV4 18,42 , some theoretical calculations have questioned whether ferritin's magnetic properties are sufficient to actuate the channels by either localized heating or mechanical force 24 , as has been proposed. Additionally, follow-up studies of the TRPV4-ferritin platform by Wang et al 43 , Xu et al 44 , and Kole et al 45 , all using electrophysiological readouts, have been unsuccessful in recapitulating the results by Wheeler et al 18 , leading others to suggest alternative physical mechanisms that may account for the growing body of empiric data 42,46,47 . However, none of these studies proposed a possible chemical mechanism, a possibility that was tested here using chemical inhibitors or quenchers of reactive oxygen species generation.…”
Section: Discussionmentioning
confidence: 99%
“…While several groups have reproduced the key observation that a sufficiently strong magnetic field can gate TRPV1 [15][16][17] and TRPV4 18,42 , some theoretical calculations have questioned whether ferritin's magnetic properties are sufficient to actuate the channels by either localized heating or mechanical force 24 , as has been proposed. Additionally, follow-up studies of the TRPV4-ferritin platform by Wang et al 43 , Xu et al 44 , and Kole et al 45 , all using electrophysiological readouts, have been unsuccessful in recapitulating the results by Wheeler et al 18 , leading others to suggest alternative physical mechanisms that may account for the growing body of empiric data 42,46,47 . However, none of these studies proposed a possible chemical mechanism, a possibility that was tested here using chemical inhibitors or quenchers of reactive oxygen species generation.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, Wheeler et al used the recorded action potentials as the primary evidence to argue that Magneto2.0 serves as a magnetic actuator (and its surface expression) 2 , yet these electrophysiology recordings were poorly controlled and confounded by spontaneous action potentials. Thus, the rigorous electrophysiology experiment that is essential for validating Magneto as a magnetic actuator remains missing (also see 11 with data suggestive of the endoplasmic reticulum as the source of minimal intracellular Ca 2+ elevation). Indeed, with the location of stimulating magnets continuously monitored, multiple independent electrophysiological experiments in this study (some using the exact same magnetic stimulations and/or tissues prepared for Wheeler et al), together with those in the two accompanied studies 9,10 , consistently demonstrated that Magneto did not respond to magnetic stimuli with any membrane depolarization (let alone action potential firing).…”
Section: Discussionmentioning
confidence: 99%
“…The master mold for the flow layer (adapted from Duret et al [32]) was 3D-printed with 1mm tall channels (Form 2, Flexible Resin, Formlabs). After curing the PDMS for the bottom flow layer (thereby embedding the immobilization chamber), holes were punched for inlet/outlet access for the flow layer.…”
Section: Microfluidic Device Fabricationmentioning
confidence: 99%